Financial Viability and Adoption of the Zecc Technology for Tomato Storage in Savelugu and Sagnarigu Municipalities in the Northern Region of Ghana - Essel, E.A. (University Of Ghana, 2018)
Zero Energy Cool Chamber (ZECC) storage technology is the use of an evaporative cool chamber for maintaining low temperature of fruits and vegetables compared to field, shed and room temperature. In order to help farmers and traders, the ZECC technology was introduced in the Savelugu and Sagnarigu municipalities. However, only a few of the farmers and traders have adopted it in these municipalities. Although the ZECC seems to be a means to help solve storage challenges, the validity of the farmers’ and traders’ perception of high cost relative to returns in the usage of the ZECC cannot be ascertained. This study, therefore, sought to examine the levels of awareness and usage of the ZECC, compare the net benefits of the ZECC with the existing storage method, the factors that would influence them in adoption of the ZECC, and finally identify constraints that affect farmers and traders in using the ZECC. A multistage sampling method was employed to select 210 farmers and traders in the municipalities. The study used descriptive statistics such as frequencies, percentages, likert scale, the benefit-cost analysis, probit, and the Kendall’s coefficient of concordance (W) to address the objectives. Findings indicated that 83.33% of the respondents were aware of the ZECC technology but 26.19% have adopted the ZECC. The study revealed an NPV of GHS6, 436.15 and BCR of 1.52 for ZECC; and an NPV of GHS2, 699.41 and BCR of 1.09 for the existing method at 21% discount rate. With the exception of location, marital status and age, remaining factors were statistically significant to influence adoption of the ZECC. Among the constraints identified, access to credit and animal disturbances were ranked as the first and second most pressing constraints, respectively for farmers. High cost of transportation and high cost of storage were the first two most pressing constraints, in order of priority for traders. In conclusion, most of the respondents were aware of the ZECC but do not see the need for its usage, even though the ZECC proves to be more cost effective. It is, therefore, recommended, among others, that agricultural training institution and NGOs should organize sensitization programmes and training sessions for farmers and traders on the ZECC. Additionally, developmental agencies should tailor their development plans and projects towards addressing these challenges that hinder the ZECC usage in the Northern Region of Ghana.
MPhil.
Keywords: Zecc Technology; Tomato; Savelugu; Sagnarigu; Northern Region